(untitled) (Canadian Medical Education Journal, 2024)
Implication Statement We present a novel small group teaching format (termed IDEA-R), ideal for deliberate targeting and escalation of cognitive learning tasks. Additionally, this approach is ideal for smaller postgraduate programs which struggle to predict trainee attendance far in advance, as it provides a flexible format that can adapt to in-the-moment fluctuations in trainee numbers.